Newcastle disease virus expressing clade 2.3.4.4b H5 hemagglutinin confers protection against lethal H5N1 highly pathogenic avian influenza in BALB/c mice - Kim, Deok-Hwan; Lee, Seung-Hun; Kim, Jiwon; Lee, Jiho; Lee, Ji-Hun; Jeong, Jei-hyun; Kim, Ji-yun; Choi, Yang-Kyu; Youk, Sungsu; Song, Chang-Seon (Frontiers in Veterinary Science, 2025)
The widespread H5 clade 2.3.4.4b highly pathogenic avian influenza virus (HPAI) poses a significant threat to both domestic and wild mammals because of its rapid genetic evolution, cross-species transmissibility, and host-range expansion. The increasing number of cases in mammalian species highlights the need for proactive measures driven by the One Health approach. In this study, we explored the potential use of previously developed a Newcastle disease virus (NDV)-vectored vaccine expressing clade 2.3.4.4b H5 hemagglutinin (rK148/22-H5) in a preclinical BALB/c mouse model. Two doses of intramuscular vaccination with viable (107 EID50/0.1 mL) or inactivated (107 EID50/0.1 mL) rK148/22-H5 provided protection against lethal H5N1 HPAI. A greater than 100-fold reduction in lung viral load was observed in the rK148/22-H5 vaccinated group compared to the control group. Consistently, co-housed contact mice in the vaccine group survived without evidence of infection, whereas those in the control group became infected and succumbed to the disease. The rK148/22-H5 vaccine demonstrated potential as a HPAI vaccine candidate for mammals, warranting further steps to advance this candidate vaccine into clinical trials in domestic and captive mammalian species.